Schiff bases complexed with iron and their relation with the life cycle and infection by Schistosoma mansoni - da Silva, Juliana Virginio; Moreira, Carla Cristina; Montija, Elisandra de Almeida; Feitosa, Karina Alves; Correia, Ricardo de Oliveira; Domingues, Nelson Luis de Campos; Soares, Edson Garcia; Allegretti, Silmara Marques; Afonso, Ana; Anibal, Fernanda de Freitas (Frontiers in Immunology, 2022)
The trematode Schistosoma mansoni causes schistosomiasis, and this parasite's life cycle depends on the mollusk Biomphalaria glabrata. The most effective treatment for infected people is administering a single dose of Praziquantel. However, there are naturally resistant to treatment. This work has developed, considering this parasite's complex life cycle. The synthetics compound were evaluated: i) during the infection of B. glabrata, ii) during the infection of BALB/c mice, and iii) during the treatment of mice infected with S. mansoni. For the first objective, snails infected with miracidia treated with compounds C1 and C3 at concentrations of 25% IC50 and 50% IC50, after 80 days of infection, released fewer cercariae than the infected group without treatment. For the second objective, compounds C1 and C3 did not show significant results in the infected group without treatment. For the third objective, the mice treated with C3 and C1 reduced the global and differential cell count. The results suggest that although the evaluated compounds do not present schistosomicidal properties when placed in cercariae suspension, they can stimulate an immune reaction in snails and decrease mice's inflammatory response. In general, we can conclude that compound C1 and C3 has an anti-schistosomicidal effect both in the larval phase (miracidia) and in the adult form of the parasite.